Planners in the Future City: Using City Information Modelling to Support Planners as Market Actors - Emine Mine Thompson; Paul Greenhalgh; Kevin Muldoon-Smith; James Charlton; Michal Dolník (Urban Planning, 2016)
Recently, Adams and Tiesdell (2010), Tewdwr-Jones (2012) and Batty (2013) have outlined the importance of information and intelligence in relation to the mediation and management of land, property and urban consumers in the future city. Traditionally, the challenge for urban planners was the generation of meaningful and timely information. Today, the urban planners’ challenge is no longer the timely generation of urban data, rather, it is in relation to how so much information can be exploited and integrated successfully into contemporary spatial planning and governance. The paper investigates this challenge through a commentary on two City Information Modelling (CIM) case studies at Northumbria University, UK. This commentary is grouped around four key themes, Accessibility and availability of data, accuracy and consistency of data, manageability of data and integration of data. It is also designed to provoke discussion in relation to the exploitation and improvement of data modelling and visualisation in the urban planning discipline and to contribute to the literature in related fields. The paper concludes that the production of information, its use and modelling, can empower urban planners as they mediate and contest state-market relations in the city. However, its use should be circumspect as data alone does not guarantee delivery of a sustainable urban future, rather, emphasis and future research should be placed upon interpretation and use of data.